2005
DOI: 10.1016/s1726-4901(09)70247-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pregnancy and Partial Recovery of Pituitary Function in a Patient with Sheehan's Syndrome

Abstract: Sheehan's syndrome is caused by pregnancy-related hemorrhage leading to ischemic necrosis of the anterior pituitary gland and hypopituitarism. Spontaneous pregnancy in Sheehan's syndrome is very rare. We report the case of a patient with Sheehan's syndrome who suffered from anterior pituitary insufficiency, but with sparing of gonadotropic function. The patient became pregnant spontaneously and, after her second delivery, thyrotropic function recovered. However, the patient's growth hormone and cortisol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…[24–26] Similarly, partial recovery of pituitary function has also been reported. [27] Hyponatremia is the most common electrolyte disturbance occurring in 33–69% of all cases. Several mechanisms are responsible for hyponatremia.…”
Section: Anterior Pituitary Dysfunctionmentioning
confidence: 99%
“…[24–26] Similarly, partial recovery of pituitary function has also been reported. [27] Hyponatremia is the most common electrolyte disturbance occurring in 33–69% of all cases. Several mechanisms are responsible for hyponatremia.…”
Section: Anterior Pituitary Dysfunctionmentioning
confidence: 99%
“…There was only 1 single case reported partial recovery of hypothalamus-pituitary-thyroid (HPT) axis of a patient with Sheehan's Syndrome in the previous study. 9 In our case, the patient's HPA axis was blunted after the pituitary macroadenoma surgery. Before her pregnancy, the peak value of serum cortisol in the insulin tolerance test was 11.05 μg/dl; however, after the delivery, the serum cortisol showed a well response to the insulin tolerance test (Figure 2 ).…”
Section: Discussionmentioning
confidence: 51%
“…Spontaneous pregnancy in patients with pituitary dysfunction were only reported in partial hypopituitarism patients with normal gonadal function, most commonly in Sheehan's syndrome or lymphocytic hypohysitis. 9 , 10 Panhypopituitarism patients could not be spontaneous pregnant, clinical practice of ovulation–induction treatment including administration of hCG and follicle-stimulating hormone, pulsatile GnRH, and in vitro fertilization, enabled the hypopituitary women to become ovulation and pregnancy. However, limited experience showed that the success rate was less lower than other no ovulation infertility.…”
Section: Discussionmentioning
confidence: 99%
“…So pregnancy is propitious to the patients with Sheehan's syndrome, but it could improve the symptoms as well. See et al [15] reported that spontaneous pregnancy could bring partial recovery of pituitary function in the patient with Sheehan's syndrome. However, in this case, the symptoms of Sheehan's syndrome got worse after the fourth spontaneous pregnancy.…”
Section: Discussionmentioning
confidence: 99%